ChemInform Abstract: Highly Porous Organic Polymer Containing Free ‐CO2H Groups: A Convenient Carbocatalyst for Indole C—H Activation at Room Temperature. Issue 46 (24th October 2013) - Modak, Arindam; Mondal, John; Bhaumik, Asim
Abstract The heterogeneous title catalyst bears a high concentration of active COOH sites.